PENUNDAAN PEMILIHAN UMUM DALAM PERSPEKTIF DEMOKRASI - Yudi Widagdo Harimurti (Trunojoyo Madura University, 2022)
In the implementation of a democratic state, the implementation of what is commonly called a General Election is needed, especially in representative government. This is because the government’s authority is only obtained with the approval of the governed (the people). Democratic elections are not just simbols, the are competitive, periodic, inclusive and definitive elections. The legality of people’s involvement in the success of democratic parties in Indonesia, as regulated by Article 22 E of the 1945 Constitution of the Republic Indonesia. This research is a normative research, using statute approach and historical approach and analysis using the deductive method. The result of this research is that general elections in Indonesia should be held regularly, continuously and temporarily, especially in a presedential system of government. The consequence is that there is no postponement of the election, considering that the country is not in state of emergency (staatsnoodrecht or noodstaatsrecht). It means that the purpose of this research is to hold elections to fill public positions, namely the President and Vice President, the People’s Representative Council (DPR) and the Regional Representative Council (DPD).